Further evidence that CP-AMPARs are critically involved in synaptic tag and capture at hippocampal CA1 synapses - Pojeong Park; Heather Kang; John Georgiou; Min Zhuo; Bong-Kiun Kaang; Graham L. Collingridge (Molecular Brain, 2021)
Abstract The synaptic tag and capture (STC) hypothesis provides an important theoretical basis for understanding the synaptic basis of associative learning. We recently provided pharmacological evidence that calcium-permeable AMPA receptors (CP-AMPARs) are a crucial component of this form of heterosynaptic metaplasticity. Here we have investigated two predictions that arise on the basis of CP-AMPARs serving as a trigger of STC. Firstly, we compared the effects of the order in which we delivered a strong theta burst stimulation (TBS) protocol (75 pulses) and a weak TBS protocol (15 pulses) to two independent inputs. We only observed significant heterosynaptic metaplasticity when the strong TBS preceded the weak TBS. Second, we found that pausing stimulation following either the sTBS or the wTBS for ~20 min largely eliminates the heterosynaptic metaplasticity. These observations are consistent with a process that is triggered by the synaptic insertion of CP-AMPARs and provide a framework for establishing the underlying molecular mechanisms.